Clinical and laboratory profile of dengue fever: a retrospective study - Solanke, Sachin N.; Pohekar, Abhay S.; Pohekar, Jayshree A. (International Journal of Advances in Medicine, 2019)
Background: The global incidence of dengue has grown dramatically in recent decade. Half of world’s population is now at risk. India represents significantly a larger burden, accounting for nearly 34% of the global burden of dengue infection. Dengue infection needs to be addressed as a single disease with different clinical presentations ranging from asymptomatic conditions to severe clinical courses that may lead to high morbidity and mortality. Method: This was retrospective observational study carried out during period of July 2017 to April 2018, to study clinical profile and laboratory parameters in dengue fever patients. Confirmed dengue cases having NS1 positive or IgM positive or having both NS1 and IgM positive or dengue ELISA reactive, having minimum one CBC reports done and not having other confounding factor such as co-infection, bone marrow diseases etc. that may altered clinical and laboratory results are included in study. Statistical analysis was done by SPSS software version 18.0. Results: Out of 48 confirmed dengue cases maximum patients 58.33% was from young age group (21 to 40 years) with M:F ratio was 2.43:1. Fever was found in 100% patients, in order of frequency followed by headache, bodyache, abdominal pain, weakness, retro-orbital pain, anorexia, dry cough, back pain, nausea, diarrhoea, vomiting, rash, joint pain, itching and malena.NS1was positive in 41.67% cases, dengue ELISA in 31.25%, IgM was positive in 20.83% cases, and both NS1 and IgM positive were in 4.17% cases. TLC count was low 35.42%, high in 12.50% of cases and remaining had normal TLC count. Platelet count was ranged between normal platelet counts to thrombocytopenia. One case had platelet count less than 20000. Out of 48 patients, 2 (4.17%) had malena. Conclusion: In this study, fever was found in all patients, and headache, body ache and weakness were common symptoms, but significant number of patients also had gastroentstinal and respiratory symptoms like abdominal pain, nausea, diarrhea, vomiting and dry cough. TLC count ranging from normal TLC, leukopenia to leucocytosis. Large number of patients had low platelet count that shows dengue fever had varied clinical presentation.